Analysis of the Vacancy System of Restructured Zinc by the Positron Annihilation Method; Technical Physics; Vol. 63, iss. 6 - Solovjev E. M.; Spitsyn B. V. Boris Vladimirovich; Laptev R. S. Roman Sergeevich; Lider A. M. Andrey Markovich; Bordulev Yu. S. Yury Sergeevich; Mikhaylov A. A. Andrey Anatoljevich (2018, 2018)
Title screen